SIU-ICUD: Germline Genetic Susceptibility to Prostate Cancer: Utility and Clinical Implementation - James T. Kearns; Annabelle Ashworth; Elena Castro; Rosalind A. Eeles; Liesel M. FitzGerald; Peter J. Hulick; Stacy Loeb; Christian P. Pavlovich; Timothy R. Rebbeck; Susan T. Vadaparampil; Zhuqing Shi; Huy Tran; et al. (Société Internationale d’Urologie Journal, 2025)
Background/Objectives: Prostate cancer is the most common cancer among men globally and a leading cause of cancer-related death. Germline genetic evaluation is increasingly recognized as essential for men with high-risk features such as a strong family history or advanced disease. Methods: Comprehensive genetic risk assessment should integrate three components: family history (FH), rare pathogenic mutations (RPMs), and polygenic risk scores (PRS). RPMs in DNA repair genes (e.g., BRCA2, CHEK2, ATM) can inform screening, prognosis, and treatment strategies, particularly for metastatic or aggressive disease. PRS, derived from common genetic variants, provides a personalized and independent measure of prostate cancer risk and may guide decisions on screening intensity and timing. Results: Although PRS cannot yet differentiate between indolent and aggressive cancer, it has the potential to stratify men into low and high-risk categories more effectively than FH or RPMs alone. Knowledge of specific RPMs can influence treatment decisions in clinically advanced prostate cancer. Challenges in clinical implementation include limited provider awareness, underutilization of genetic counseling, and lack of diversity in genomic datasets, which can lead to misdiagnoses. Emerging technologies and digital tools are being developed to streamline genetic testing and counseling. Population-level strategies and tailored screening protocols based on genetic risk are under active investigation. Conclusions: While early evidence suggests high satisfaction with genetic testing among patients, further studies in diverse populations are needed. Integration of germline genetic information into prostate cancer management offers promising avenues for personalized screening, surveillance, and treatment, ultimately aiming to reduce morbidity and mortality.